2021
DOI: 10.3928/02793695-20201015-01
|View full text |Cite
|
Sign up to set email alerts
|

Does Psychosocial Functioning Improve With Prolonged Exposure in Veterans With PTSD?: Exploring Traditional and Home-Based Telehealth Delivery Methods

Abstract: The current study explored whether prolonged exposure (PE), delivered in person or via home-based telehealth, had a therapeutic effect on psychosocial functioning in combat Veterans with posttraumatic stress disorder (PTSD). The effects of home-based telehealth on these metrics were also evaluated. In addition, we examined whether race, type of war conflict, and service-connected disability rating moderated the effect of PE on psychosocial functioning and whether PTSD, anxiety, and/or depression mediated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Improvements in PTSD with exposure therapy were associated with improvements in psychosocial functioning. 34,35 Therefore, the reduction of PTSD symptoms through WET was expected to improve general functioning. Previous research has not reported on the improvement of functioning through WET; therefore, it is significant that the improvement of general functioning after WET was identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in PTSD with exposure therapy were associated with improvements in psychosocial functioning. 34,35 Therefore, the reduction of PTSD symptoms through WET was expected to improve general functioning. Previous research has not reported on the improvement of functioning through WET; therefore, it is significant that the improvement of general functioning after WET was identified in this study.…”
Section: Discussionmentioning
confidence: 99%